The effect of three-month aerobic training on the expression of AIF and caspase-9 gene in male rat soleus muscle - Neda Abadi; Jabbar Bashiri (Fasa University of Medical Sciences, 2017)
Background & Objectives: Apoptosis in skeletal muscle plays an important role in disease-related tissue dysfunction such as muscle atrophy. Current evidence suggests that exercise training may alter apoptosis-related signaling and enzymes in skeletal muscle. Therefore, the purpose of this study was to investigate the effect of three-month aerobic training on AIF and caspase-9 gene expression in male rat soleus muscle. Materials & Methods: This study was conducted as a two-group experimental design and sixteen 3-month-old male rats were selected and randomly divided into two groups of aerobic training (n=8) and control (n=8). Rats in trained group participated in the aerobic training program for three months (75-80%). 48 hours after the last training session, the soleus muscle of rats were extracted and AIF and caspase-9 mRNA were evaluated by Real Time-PCR. Independent-samples t-test was applied to analyze the data (P<0.05). Results: AIF gene expression of trained group was significantly higher than that of the control group (137.60%, P=0.01). Furthermore, caspase-9 gene expression of trained group was significantly higher than that of the control group (48.22%, P=0.01). Conclusion: In general, it seems that a three-month aerobic training was effective in increasing soleus muscle mitochondrial apoptotic protein. However, more research needs to be done to identify the effects of exercise trainings on indices of apoptosis and skeletal muscle atrophy.